The impact of learning analytics technology acceptance on teaching decision-making among secondary school teachers in Chongqing, China - Wang, Qian; Aida Hanim A. Hamid (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examines factors influencing Learning Analytics Technology (LAT) acceptance among secondary school teachers in Chongqing, China, and investigates its relationship with teaching decision-making. This research employed a quantitative cross-sectional design and collected data from 341 teachers (197 urban, 144 rural) using a structured questionnaire. Descriptive statistics revealed moderately high overall LAT acceptance (M=3.68, SD=0.79), with significant differences between urban (M=3.92, SD=0.65) and rural teachers (M=3.44, SD=0.78). Correlation analysis identified strong associations between LAT acceptance and teacher training (r=0.624, p<0.001), management support (r=0.581, p<0.001), and technology availability (r=0.537, p<0.001), with peer influence showing a moderate relationship (r=0.429, p<0.001). LAT usage demonstrated a significant positive correlation with teaching decision-making efficacy (r=0.578, p<0.001), particularly with decision quality (r=0.594, p<0.001). This relationship was stronger among urban teachers (r=0.612, p<0.001) than rural counterparts (r=0.524, p<0.001), highlighting an urban-rural divide in educational technology benefits. The findings provide empirical evidence for educational administrators and policymakers seeking to enhance LAT implementation in secondary schools, suggesting that comprehensive approaches addressing professional development, institutional support, and technological infrastructure are essential for effective LAT adoption, with particular attention needed to reduce urban-rural disparities.